Sensory analysis of handmade beers from Paragominas-PA (Research, Society and Development, 2022)
Craft beer is that produced by less industrialized methods, prioritizing quality over quantity. Its popularization in the Brazilian market grows exponentially based on the number of breweries registered in Brazil each year. The objective of this work was to perform sensory analyses of 4 styles of artisanal beers of local manufacture through acceptance tests by hedonic scale and purchase intention test. The beers studied were produced by the country brewery, being Pilsen, APA, IPA, and Stout. Sixty untrained volunteer tasters participated in the tests, all of them of age, half of them male and the other half female, all beer drinkers, who had good health conditions. To evaluate the similarity or difference on each parameter evaluated between beers, the Kruskal-Wallis test was performed on the means, considering a significance level of 5%. For the comparison of means, the Nemenyi test was performed, which connected the statistically similar means. Although most participants claim to know the difference between traditional beers and craft beers, and consume craft beer, most of them still show indifferent preference among these options. The most accepted beer for the studied public was Pilsen, the least accepted was Stout. This result is reflected in the purchase intent test. With Pilsen having the highest average, while Stout had the lowest.